If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -40 = 45 Reorder the terms: -40 + 6x = 45 Solving -40 + 6x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 6x = 45 + 40 Combine like terms: -40 + 40 = 0 0 + 6x = 45 + 40 6x = 45 + 40 Combine like terms: 45 + 40 = 85 6x = 85 Divide each side by '6'. x = 14.16666667 Simplifying x = 14.16666667
| -6(4p+3)-49=5(2p+7) | | 4x^2=-24-20x | | 4.2x+31.5=-65.1 | | -86=4+10x | | 3.9x-13=1.7x+31 | | w^2+4w-124=0 | | 5/9(k-273.15) | | p=9+1.5(3) | | d/4-5 | | 3x+3x+4x=5 | | p=9+1.5(1) | | 3x+3x+4x/10=5 | | 7.2x-60=3.6x+30 | | x+4=-18 | | 6-14b=22 | | 2.3x+75.5=8.8x-22 | | 3-4x=-7-4s | | -2=(6+x)/10 | | 13x+14y=177 | | -18x=0 | | =-2(-y)(y) | | 4x-(3x-7)=2x-6 | | 6=z+2/3 | | 0.3-(2x+9)=0.6x | | 16x-72=18x+14 | | 56+3x-24-63=45x-14x+22 | | p=1/2(2x)(x+3) | | 13x+14y=178 | | .1-.01(x+2)=-.03(4-x) | | 9x+10/7=4x+1/2 | | 25x-10=3x-9 | | 5x+6x-8x-5=13 |